Translating relational conceptual schema to object-oriented schema - Soon, Lay Ki (2001)
A multidatabase is a confederation of preexisting distributed, heterogeneous, and autonomous database system. The integration process is essential in the effort of forming a distributed, heterogeneous database system. This process generally consists of two main phases, which are conceptual schema translation phase and followed by the integration phase. In our research, we have proposed an alternative translation approach to convert relational database schema to object--oriented database schema. The translation approach consists of a set of translation rules, which are based on inclusion dependencies, key attributes and types of attributes. A database schema translation tool prototype, called RETOO (Relational-to-Object-Oriented) is then developed based on the proposed translation approach. RETOO receives a relational database schema as input data and generate an object-oriented database schema as the output data.RETOO operates semi-automatically, especially in the process of identifying operations for each class. This is because relational data model does not provide the behavioural information of every entity. The translation approach and RETOO database translation tool prototype are not only able to maintain the semantics of the relational database schema, but also enhance the semantics of the translated object-oriented schema via object-oriented data modelling concepts.